Nepal Social Protection : Review of Public Expenditure and Assessment of Social Assistance Programs, Main Report FY11-FY20 - World Bank (World Bank, Kathmandu, 2021)
Nepal’s recent transition to a federal state structure provides a historic juncture to realize the role that social protection can play in achieving the constitutional goals of equity, inclusion, and prosperity. The transition to a federal structure of governance and the promulgation of a new Constitution founded on the principles of equity, inclusion, and prosperity for all have brought about tremendous expectations for the previously marginalized and discriminated poor and vulnerable segments of the population. Social protection (SP) programs, which have been proven to contribute to poverty reduction and inclusive growth, have the potential to play a significant role in meeting these expectations and realizing the objectives of federalism. The report is structured as follows, with each chapter concluding with a set of recommendations based on the analysis. Chapter 2 Provides an overall analysis of social protection expenditure trends, an assessment of ability of social assistance programs; Chapter 3 Assesses the policy and institutional framework for design and delivery of social protection programs in the decentralized federal context; and Chapter 4 Provides an overview of planning, budgeting, fund flow, and reporting processes for social protection programs at federal, province, and local levels.